Climate Change Policy under Polar Amplification - William A. Brock; Anastasios Xepapadeas (Fondazione Eni Enrico Mattei (FEEM), 2016)
Polar amplification is an established scientific fact which has been associated with the surface albedo feedback and to heat and moisture transport from the Equator to the Poles. In this paper we unify a two-box climate model, which allows for heat and moisture transport from the southern region to the northern region, with an economic model of welfare optimization. Our main contribution is to show that by ignoring spatial heat and moisture transport and the resulting polar amplification, the regulator may overestimate or underestimate the tax on GHG emissions. The direction of bias depends on the relations between marginal damages from temperature increase in each region. We also determine the welfare cost when a regulator mistakenly ignores polar amplification. Finally we show the adjustments necessary to the market discount rate due to transport phenomena as well as how our two-box model can be extended to Ramsey-type optimal growth models. Numerical simulations confirm our theoretical results.
Keywords: Q54; Q58; 330; Polar Amplification; Spatial Heat and Moisture Transport; Optimal Policy; Emission Taxes; Market Discount Rate